The structural, stratigraphic and lithological control of underground water distribution in the Fraserburg district, C.P. - Wilke, P. P.(Petrus Philippus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1961.